ANALISIS PERBEDAAN JANUARY EFFECT DAN ROGALSKY EFFECT PADA PERUSAHAAN YANG TERGABUNG DALAM JAKARTA ISLAMIC INDEX DI BURSA EFEK INDONESIA TAHUN 2011 – 2013 - Nursanti, Devita (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
January effect and Rogalsky effect is one of market anomaly that could occur in the capital market. January effect is a condition in which return in January tend to be higher than average returns in other months of the year. Rogalsky effect is a phenomena where negative returns at Monday effect to disappear on specific month. The purpose of this analysis was to determine the difference between stock return in January and returns of months other than January and analysis was to determine the difference between stock return in April and returns of months other than April. The population in this study are all companies listed on the Jakarta Islamic Index in the Indonesian Stock Exchange in 2011 until 2013. Of the 30 companies listed in the Jakarta Islamic Index a sample of 11 companies. The analysis technique used was purposive sampling method. Analysis technique used is One Way ANOVA test. Results shows that there are no difference between returns in January and returns of months other than January and no differences between returns in April and returns of months other than April in the Jakarta Islamic Index. It can be concluded that in the Jakarta Islamic Index January effect and Rogalsky effect does not occur. Keywords: january effect, Rogalsky effect, stock returns